Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832) - Shimose, Tamaki; Suzuki, Nobuaki; Iwatsuki, Yukio (Zootaxa, 2020)
Platyinius amoenus Snyder 1911 has long been considered a junior synonym of Pristipomoides argyrogrammicus (Valenciennes 1832), however, the two are discernible as distinct species from color patterns and counts of gill rakers based on examination of their type materials and non-type specimens. Furthermore, genetic differences based on molecular analysis among the two species (mtDNA, COI gene) strongly support the validity of both species. Pristipomoides amoenus can be readily distinguished from P. argyrogrammicus in having no white margin to the dorsal, anal, and caudal fins, silvery blue spots continuing inside dorso-lateral yellow blotches, and presence of modally10 (vs. modally 12) lower gill rakers. Both species were collected sympatrically around Ishigaki Island, Okinawa, Japan.